Humic Acid for Reducing Carbofuran Content of Rice Grown in Carbofuran-Contaminated Soil - Reginawanti Hindersah; Betty Natalie Fitriatin; Triyani Dewi; Dedi Nursyamsi (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2023)
Carbofuran insecticide widely used in rice production. The carbofuran residue in agricultural threatens wide life and human health since its active ingredient carbamate is toxic. Humic acid (HA) amendment is an effective way to minimize the residue in soil since HA can adsorb the organic pollutant and induce growth of fungus that degrade the carbofuran. The objective of this research was to observe the influence of HA on the carbofuran residues in soil, straw, and rice; as well as yield of paddy (Oryza sativa L.) grown in carbofuran contaminated potted soil. The level of carbofuran residue in soil before experiment was 10 mg kg-1. The experiment was setup in Randomized Block Design to test various HAs extracted from organic matter. The results indicated that humic acid didn’t affect plant growth and yield but decreased the carbofuran residue in straw and unhusked rice grain. Rhizosphere of rice treated with HA showed higher fungal count than control. This experiment suggests that HA were effectively used to control the carbofuran residue in soil and rice grown in low carbofuran-contamination agricultural soil